Solve the system:
1 Answer | Add Yours
To solve the equation, we solve the second equation for x. `x-6y=-4->x=6y-4`
Now we substitute our value for x, into the first equation.
We simplify and we get
Combine like terms, and solve for 0
The most obvious answer is that y=0, and that is one solution. The other value is found by rewriting the equation:
we divide each side by y and get
We solve for y by dividing 48 by 32 and `y=48/32=3/2=1 1/2`
now we substitute these y values back into one of our original equations to get x values.
So our answers are ``and `x=-4, 5`` `
Or in ordered pairs (-4,0) and (5, 1.5)
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes